How Long is a Spell of Unemployment? - Frank, Robert H. (Econometrica, 1978)
[Techniques are described whereby the distribution of completed unemployment spell lengths may be inferred from the distribution of in-process unemployment spell lengths recorded each month in the Current Population Survey. An extension is proposed whereby the complete population joint distribution of labor market transition probabilities can be estimated using only Current Population Survey information.]